2020
DOI: 10.3390/nu12010133
|View full text |Cite
|
Sign up to set email alerts
|

The Evolving Microbiome from Pregnancy to Early Infancy: A Comprehensive Review

Abstract: Pregnancy induces a number of immunological, hormonal, and metabolic changes that are necessary for the mother to adapt her body to this new physiological situation. The microbiome of the mother, the placenta and the fetus influence the fetus growth and undoubtedly plays a major role in the adequate development of the newborn infant. Hence, the microbiome modulates the inflammatory mechanisms related to physiological and pathological processes that are involved in the perinatal progress through different mecha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
96
0
8

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 115 publications
(104 citation statements)
references
References 164 publications
(210 reference statements)
0
96
0
8
Order By: Relevance
“…Such an acquired diabetogenic condition is functional and induces maternal physiological hyperglycemia, which, in turn, increases glucose availability for the growing fetus. Therefore, significant changes in the maternal gut microbiota occur during pregnancy (2,4,11). Although scholars have explored the maternal microbiota in the third trimester of pregnancy, data on the changes in maternal microbiota during early pregnancy are scarce (2,4,11,12).…”
Section: The Maternal Microbiota and Pregnancy Outcomes The Gastrointmentioning
confidence: 99%
See 3 more Smart Citations
“…Such an acquired diabetogenic condition is functional and induces maternal physiological hyperglycemia, which, in turn, increases glucose availability for the growing fetus. Therefore, significant changes in the maternal gut microbiota occur during pregnancy (2,4,11). Although scholars have explored the maternal microbiota in the third trimester of pregnancy, data on the changes in maternal microbiota during early pregnancy are scarce (2,4,11,12).…”
Section: The Maternal Microbiota and Pregnancy Outcomes The Gastrointmentioning
confidence: 99%
“…The gut microbiota in the first trimester of pregnancy resembles the microbiota of healthy nonpregnant women (2,4,11). Women have unique gut microbiota that can be classified into different classes or enterotypes.…”
Section: The Maternal Microbiota and Pregnancy Outcomes The Gastrointmentioning
confidence: 99%
See 2 more Smart Citations
“…The other reviews have described the intestinal microbiota changes in specific conditions, early infancy, hepatic ischemia-reperfusion and regeneration in liver surgery, vaginal microbiota, and cardiovascular diseases. Mesa et al [20] reported the microbiome changes and how those modulate the inflammatory mechanisms related to physiological and pathological processes that are involved in the perinatal progress. Cornide-Petronio et al [21] summarized the role of starvation, supplemented nutrition diet, nutritional status, and alterations in microbiota on hepatic ischemia/reperfusion and regeneration.…”
mentioning
confidence: 99%